2017
DOI: 10.1002/brb3.868
|View full text |Cite
|
Sign up to set email alerts
|

Brain lesions affecting gait recovery in stroke patients

Abstract: ObjectivesGait recovery is an important goal in stroke patients. Several studies have sought to uncover relationships between specific brain lesions and the recovery of gait, but the effects of specific brain lesions on gait remain unclear. Thus, we investigated the effects of stroke lesions on gait recovery in stroke patients.Materials and MethodsIn total, 30 subjects with stroke were assessed in a retrograde longitudinal observational study. To assess gait function, the functional ambulation category (FAC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…Voxel-based lesion-symptom mapping is a neuroimaging technique that can be used to study the relationship between tissue damage and behavior on a voxel-by-voxel basis. VLSM has been widely used to identify lesion-symptom relationships in stroke patients, and has been used extensively to study, among other functions, language [ 16 ], gait [ 17 ], and spasticity [ 18 ]. A recent study a recent study by Suntrup-Krueger et al [ 19 ] demonstrated via VLSM the role of specific cortical lesions with impaired RC in stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…Voxel-based lesion-symptom mapping is a neuroimaging technique that can be used to study the relationship between tissue damage and behavior on a voxel-by-voxel basis. VLSM has been widely used to identify lesion-symptom relationships in stroke patients, and has been used extensively to study, among other functions, language [ 16 ], gait [ 17 ], and spasticity [ 18 ]. A recent study a recent study by Suntrup-Krueger et al [ 19 ] demonstrated via VLSM the role of specific cortical lesions with impaired RC in stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis of 24 studies using fMRI of motor tasks, Favre et al ( 2014 ) affirmed that the activity in ipsilateral primary motor cortex is one of the best predictors of the good motor recovery in chronic stroke patients. Similarly, connectivity (i.e., DTI) as well as lesion mapping studies demonstrated that the disruption of the capsula interna, corona radiata, globus pallidus, and putamen predict the functional recovery (Shelton and Reding, 2001 ; Rehme et al, 2011 ; Stinear et al, 2012 ; Stinear and Ward, 2013 ; Hannanu et al, 2017 ; Lee et al, 2017 ). The pathway along the pedunculopontine nucleus, cerebellum, striatum and the motor cortex contributes to motor initiation, modulation of motor rhythm and postural muscle tone during motor behaviors (Takakusaki, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some biomarkers have been effectively demonstrated to predict therapeutic response or recovery following stroke (Burke Quinlan et al, 2015 ). Generally, research has focused on the neural substrate of motor recovery obtained with a conventional neurorehabilitation approach (Shelton and Reding, 2001 ; Murphy and Corbett, 2009 ; Carrera and Tononi, 2014 ; Choo et al, 2015 ; Lee et al, 2017 ; Siegel et al, 2018 ), whereas little attention has been paid to robotic-assisted therapy with exoskeleton devices (Formaggio et al, 2013 ; Fan et al, 2016 ; Gandolfi et al, 2018 ). Overall, preservation of the corticospinal tract is considered as a hallmark for good recovery of impaired motor function in patients with brain injury (Hendricks et al, 2002 ; Swayne et al, 2008 ; Stinear, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the statistical power for identification of the lesion pattern, which showed a significant contribution to PCF independent of hemispheric lateralization, the volume-of-interest (VOI) images were transformed to the right hemisphere. To analyze the mutual lesion maps, segmentation and normalization were employed [17].…”
Section: Lesion Analysismentioning
confidence: 99%